2014
DOI: 10.1089/lap.2014.0104
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Sleeve Gastrectomy with Endoscopic Versus Bougie Calibration: Results of a Prospective Study

Abstract: Endoscopic calibration is associated with lower postoperative complications after laparoscopic sleeve gastrectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…These results suggest that EGD use may be protective against dehydration-related complications after LSG. This is consistent with existing literature, which has found lower rates of complications when an EGD is used intraoperatively 17,18. One possible explanation is the ability to directly visualize the resulting sleeve to assess for angulation, twisting, and narrowing at the incisura, which is an advantage over bougie use alone.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…These results suggest that EGD use may be protective against dehydration-related complications after LSG. This is consistent with existing literature, which has found lower rates of complications when an EGD is used intraoperatively 17,18. One possible explanation is the ability to directly visualize the resulting sleeve to assess for angulation, twisting, and narrowing at the incisura, which is an advantage over bougie use alone.…”
Section: Discussionsupporting
confidence: 89%
“…However, our results demonstrated that EGD alone, as well as a bougie coupled with EGD, had significantly lower rates of dehydration compared with bougie alone, while EGD alone compared with bougie coupled with EGD demonstrated equivalent outcomes (Table 4). Complications directly related to EGD use during LSG were not reported within our review of the literature 14–18. Adverse outcomes following EGD have been reported, including throat and abdominal discomfort, perforation, bleeding, and infection 23.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…According to published articles on IOLT for gastric cancer surgery, bariatric surgery, colorectal surgery and our own experience, we found that IOLT can be performed by gastroscopy or gastric tubes. Interestingly, researchers found that IOLT performed with gastroscopy had statistically signi cant lower PAL rates than IOLT performed with gastric tubes had (30,31). When compared with IOLT using gastric tubes, intraoperative gastroscopy had the advantage of detecting and preventing severe complications such as esophageal perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we recommend as described by Athanasiou et al that a member of the surgical team performs the intraoperative endoscopy. We feel more bariatric surgeons need to be familiar with endoscopy as this is an important adjunct to the armamentarium of a bariatric surgeon [2][3][4].…”
mentioning
confidence: 99%